Reciprocal regulation of farnesoid X receptor α activity and hepatitis B virus replication in differentiated HepaRG cells and primary human hepatocytes. Issue 9 (1st June 2016) - Radreau, Pauline; Porcherot, Marine; Ramiére, Christophe; Mouzannar, Karim; Lotteau, Vincent; André, Patrice
ABSTRACT: Hepatitis B virus (HBV) and bile salt metabolism seem tightly connected. HBV enters hepatocytes by binding to sodium taurocholate cotransporting polypeptide (NTCP), the genome of which contains 2 active farnesoid X receptor (FXR) a response elements that participate in HBV transcriptional activity. We investigated in differentiated HepaRG cells and in primary human hepatocytes (PHHs) effects of FXR activation on HBV replication and of infection on the FXR pathway. In HepaRG cells, FXR agonists (6‐ethyl chenodeoxycholic acid and GW4064), but no antagonist, and an FXR‐unrelated bile salt inhibited viral mRNA, DNA, and protein production (IC50, 0.1–0.5 mM) and reduced covalently closed circular DNA pool size. These effects were independent of the NTCP inhibitor cyclosporine‐A, which suggests inhibition occurred at a postentry step. Similar results were obtained in PHHs with GW4064. Infection of these cells increased expression of FXR and modified expression of FXR‐regulated genes SHP, APOA1, NTCP, CYP7A1, and CYP8B1 with a more pronounced effect in PHHs than in HepaRG cells. FXR agonists reversed all but one of the HBV‐induced FXR gene profile modifications. HBV replication and FXR regulation seem to be interdependent, and altered bile salt metabolism homeostasis might contribute to the persistence of HBV infection.—Radreau, P., Porcherot, M., Rami`ere, C., Mouzannar, K., Lotteau, V., André, P. Reciprocal regulation of farnesoid X receptor α activity and hepatitis B virus replication in differentiated HepaRG cells and primary human hepatocytes. FASEB J. 30, 3146–3154 (2016). www.fasebj.org